Cation distribution: a key to ascertain the magnetic interactions in a cobalt substituted Mg–Mn nanoferrite matrix. Issue 25 (16th June 2017) - Kumar, Gagan; Kotnala, R. K.; Shah, Jyoti; Kumar, Vijay; Kumar, Arun; Dhiman, Pooja; Singh, M.
Abstract : The effect of Co 2+ substitution into nanocrystalline Mg–Mn ferrite synthesized by a solution combustion technique has been studied. Abstract : The effect of Co 2+ substitution into nanocrystalline Mg–Mn ferrite synthesized by a solution combustion technique has been studied. The cation distribution has been inferred from X-ray diffraction, the magnetization technique, and Mössbauer spectroscopy. The X-ray analysis and cation distribution data have been used to investigate the detailed structural parameters such as hopping lengths, ionic radii of tetrahedral and octahedral sites, oxygen positional parameter, site bond as well as edge lengths, bond lengths, and bond angles. The variation in the theoretically predicted bond angles suggested the strengthening of the A–B super-exchange interactions, and the same has been supported by M – H and M – T, as well as by Mössbauer studies. The ZFC–FC study revealed that anisotropy increases with the incorporation of cobalt ions. The values of magneton number, theoretical lattice parameter, and Curie temperature that have been calculated by using the cation distribution are found to match well with the experimentally obtained values.